281 MORBIDITY AND MORTALITY COMPARISON FOR PATIENTS WITH HIP FRACTURES OPERATED WITHIN AND AFTER 48 HOURS. (1st January 2006) - Sircar, P.; Godkar, D.; Chambers, K.; Mahgerefteh, S.; Niranjan, S.; Cucco, R.
Abstract : Objective: To compare the morbidity and mortality of patients with hip fractures operated within and after 48 hours of the occurrence of fracture and establish if timing of repair alone had a major role in deciding how the patients fared after the surgical repair or if their preexisting comorbidities were also responsible for their postoperative outcomes. Sample: The study included the medical records of 49 patients (aged 51-99 years) admitted to Coney Island Hospital between January 2003 and January 2004 with a primary diagnosis of hip fracture who underwent surgical repair. Design: Analysis of data was done by retrospective chart review of patients admitted with the diagnosis of hip fracture to an acute care hospital setting. Patients were followed until they were transferred to rehab facility for PT/OT after their surgery. Outcome Measures: Preoperative health status of each patient was assessed using CPRI (cardiopulmonary risk index) score allocated to each individual patient, based on their comorbid conditions, and postoperative outcome was determined by complications such as bed sore, pneumonia, urinary tract infection, deep vein thrombosis, pulmonary embolism, and death. Results: Patients who underwent early surgical repair, ie, within 48 hours, had lesser complications in their postoperative period (14.7% as compared to 33.3% in the group operated beyond 48 hours). Also comparing CPRI scores of patients in each group (ie, those operated within 48 hours and those operated beyond 48 hours) with their postoperative mortality and morbidity, it appeared that there was a higher statistical correlation between CPRI scores and complications among patients in the within 48 hours group(p value .39), and an insignificant correlation among patients operated beyond 48 hours (p value .07). Conclusion: Surgical repair of hip fractures within the first 48 hours was associated with better health outcomes in a nationally representative sample, as observed in an acute care facility, irrespective of the preexisting comorbid conditions in a patient.